Pembekalan Remaja Mesjid Dari Bahaya Paham Ekonomi Sosialis Komunisme di Desa Pandau Jaya Kabupaten Kampar - WIDAYAT, PRAMA (Diklat Review : Jurnal manajemen pendidikan dan pelatihan, 2017)
Lack of debriefing to young adolescents about the dangers of socialism and communism, thus facilitating the entry of misleading doctrines. This briefing provides insight to teenage mosques to know in detail the dangers of communist socialism that can threaten anyone who crossed them. The methods used for this service are lectures and discussions, and to evaluate the results of these activities successfully or not made a pre-test or post-test questionnaire and indicators of success of the activities. The result of this activity is very useful for improving the mosque teenager's understanding of the latent danger of socialist communism, from the 90% questionnaire the expected target is achieved Keywords: Adolescent Masters, Communism, Economics Social